Total phenolic content, phytochemical screening, antioxidant and antimicrobial activities of Borassus flabellifer and Borassus aethiopum fruits - Aaron Dzigbor; David Neglo; Courage Sedem Dzah; Rosemond Sraha (Food Chemistry Advances)
This study evaluated the total phenolic content (TPC), antioxidant activity, and antimicrobial activity of both Borassus flabellifer and Borassus aethiopum fruits. TPC was determined using the Folin-Ciocalteu procedure, and antioxidant activity was evaluated using DPPH (1, 1-diphenyl–2 picrylhydrazyl) and ABTS (2, 2′-azino-bis 3-ethylbenzthiazoline-6-sulphonic acid) assays. The antimicrobial activity was investigated by measuring the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) of the fruit extracts against selected foodborne pathogens and their interaction effects when combined with standard antimicrobial drugs. TPC recorded for Borassus flabellifer was 43.5 ± 2.12 mg GAE/g dried extracts, while that for Borassus aethiopum was 23±3.54 mg GAE/g dried extract. The DPPH antioxidant activity for Borassus flabellifer and Borassus aethiopum was 28.76±0.56 % and 28.22±0.43 %, respectively, while the ABTS antioxidant activity recorded 57.37±2.85 % and 70.98±2.89 %, respectively, for Borassus flabellifer and Borassus aethiopum. The MIC and MBC of Borassus flabellifer ranged between 0.10–2.50 mg/mL and 6.25–25.00 mg/mL, respectively, while those of Borassus aethiopum ranged between 0.20–12.50 mg/mL and 12.50–25.00 mg/mL, respectively. Both fruit extracts demonstrated varied effects when combined with standard antimicrobial drugs. Thus, the consumption of Borassus fruits provides additional health benefits. However, these benefits vary with the variety of Borassus fruits.